Sistem Pakar Menggunakan Metode Backward Chaining dalam Mengidentifikasi Kandungan Senyawa Boraks, Formalin, Rhodamin B dan Metanil Yellow pada Makanan - Kholil, Muhammad Irvan; Nurcahyo, Gunadi Widi (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
This research is motivated by the increasing number of food producers using additives that are not permitted to be used or which are harmful to health. The addition of hazardous substances in food and beverages has a huge effect on health. The use of these dangerous substances can cause inflammation of the digestive tract, degeneration or wasting of the liver, odema / swelling of the brain, accumulation of fluid in the organs of the body. This analysis applies the Backward Chaining Method in the Expert System, namely by the system processing existing facts to lead to conclusions. Facts are obtained from physical conditions, also known as symptoms. Backward Chaining is goal-driven reasoning, which begins with making predictions of what will happen, then looking for evidence that supports (or refutes) the hypothesis. In the Expert System for identifying chemical compounds of borax, formalin, rhodamine b and methanyl yellow in food using the Backward Chaining Method, the results obtained from the expert's matching data with the results of which results matched 6 out of 6 data, or with a percentage of 100%. The resulting solution is that the sample must be tested for labor. It is hoped that this application can help the public in educating chemical compounds in food and identifying the initial stages of food before being reported to the Food and Drug Supervisory Agency for laboratory testing.